Correlation between hydration and basketball performance - Vukasinovic-Vesic, M.; Dikic, N.; Andjelkovic, M.; Radivojevic, N.; Curcic, D. J.; Antic, T.; Baralic, I.; Turner, R.; Stokes, R.; Gunter, H. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Many study results suggest that inadequate hydration is influencing sports performance by: impairing mental/cognitive performance, decreasing the motivation to exercise, increasing the rating of perceived exertion and decreasing the time to exhaustion. In basketball dehydration is correlated with overall basketball performance, jumps, shooting and number of shots that were attempted and made. The aim of our study was to analyze the influence of hydration on basketball performance. Method: Ninety-six basketball players of eight national teams have assessed during official FIBA Europe U20 Championship Men 2011 - Division B held in Sarajevo in July 2011. In order to detect a correlation between hydration and basketball performance we measured body mass of all players before and after one game. This correlation was evaluated by percentage of dehydration (body mass loss/pre exercise body mass) x 100. Results: Players age was 19±0.79 years. After the game percentage of dehydration was 0.99±0.7% (-1.25 - 2.95%). We found statistically significant negative correlation between percentage of dehydration with most valuable player index (MVP) (p< 0.01), points scored (p< 0.01), total rebounds (p< 0.01), shooting percentage for 3 points (p< 0.05), shooting percentage for 1 points (p< 0.05), assists (p< 0.05). Discussion: We have found that dehydration considerably impaired basketball performance. Dehydration significantly impaired points scored, total rebounds, shooting percentage for 3 points, shooting percentage for 1 point, assists, except steals balls, turnovers and shooting percentage for 2 points. Most importantly, there is a significant negative correlation between hydration and the category of the most valuable player index (MVP). We decided to use the method of percentage of dehydration because we consider that this parameter can be used most efficiently and effectively on the spot by trainers to measure hydration level of players. The result of this study showed that dehydration is not only a physiological state, but also a very important factor for the total performance of one team, which requires sports personnel to be educated in order to be able to help contribute to a better overall sports performance.